Karakteristik Perlukaan Akibat Kekerasan Tumpul Dan Kekerasan Tajam Pada Kasus Kematian Di Instalasi Forensik Abdoel Wahab Sjahranie Samarinda Tahun 2019-2022 - Vinna Dwi Hapsari; Nugroho, Hary; Putro, Heryadi Bawono (ITKES Wiyata Husada Samarinda, 2026)
Samarinda, the capital of East Kalimantan, has the highest incidence of crimes against life, as reported by the Central Bureau of Statistics. This study seeks to delineate the attributes of blunt force and sharp force injuries in mortality cases at the forensic unit of Abdoel Wahab Sjahranie Regional Public Hospital, Samarinda, from 2019 to 2022, utilizing data from VeR reports. This is a retrospective descriptive study employing a total sampling technique, comprising 94 samples. Findings indicate that blunt force injuries accounted for the majority of fatalities. In blunt force cases, the majority were adults aged 26-45 years, predominantly male, with lacerations, primarily situated on the head and face. In cases of sharp force injuries, all victims were adults aged 26 to 45 years, comprising both males and females, and exhibited chop wounds, predominantly located on the head, face, neck, chest, and back. The majority of victims in incidents of death resulting from blunt and sharp force trauma were adult males aged 26-45 years, comprising of the total, with all victims being male. Lacerations constituted the predominant injury type, predominantly situated on the head and face. The study concludes that the predominant cases involved blunt force trauma, leading to wounds of the head and face, with male victims in the adult demographic being the most impacted. Keywords: Death cases, blunt force injuries, sharp force injuries